Performance Ranking, Policy Feedback and Environmental Policy Implementation: An Empirical Study of the Mandatory Target System - Xiao Tang; Zhengwen Liu; Hongtao Yi (Review of Policy Research, 2018)
With the deterioration of the environment across the globe, environmental problems have attracted much attention from the public, academia, and governments. This study contributes to the understanding of environmental policy implementation by empirically testing the policy feedback theory and official ranking tournament theory in the Chinese context. In particular, it focuses on how prior environmental performance ranking transitions into future policy performance through the mandatory target system (MTS) in China. The results from this study show that provincial environmental performance ranking serves as an effective incentive for strengthening environmental governance. Low‐ranking provinces will improve their environmental policy performances in future years because of competition in the official tournament. Policy implications are drawn to improve the administrative design of environmental management.